Improvement of the Exon Method for Rapid Synthesis of cDNA of the Rat Renalase Gene - Fedchenko, V.I.; Kaloshin, A.A.; Medvedev, A.E. (Biomedical Chemistry: Research and Methods, 2023)
We have improved our previously developed method of exon cloning of cDNA of eukaryotic genes to obtain the rat renalase gene cDNA. In contrast to the previously used step-by-step pairwise assembly of exons, in this work the procedure of full-length cDNA preparation was shortened due to simultaneous assembly of four neighboring exons at once (exons 1-4 and exons 6-9 of the rat renalase gene). The two obtained sequences (exons 1-4 and 6-9) were combined into a full-length cDNA of the rat renalase gene. The cDNA synthesized in this way was cloned into the prokaryotic vector pET-28a(+), which was then expressed in E. coli cells. The correctness of this approach was confirmed by sequencing resultant cDNA sequencing, which showed full (100%) identity with the nucleotide sequence available in the GenBank database (accession code: GenBankNM_001014167).